anonymous
  • anonymous
If a + bi is a root of the quadratic equation x^2 + cx + d = 0, then show that a^2 + b^2 = d and 2a+c=0.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
AccessDenied
  • AccessDenied
I believe that we could use quadratic formula here, and equate the like-parts (real and imaginary): \( \Large { x = \frac{\neg b + \sqrt{b^2 - 4ac}}{2a} } \) We'll only need the positive part because x = a + bi, it is adding the bi. So, this equation would look like this: \( \Large a + bi = \frac{\neg c + \sqrt{c^2 - 4d}}{2} \) To get the imaginary part, we need to factor out a -1 from \(c^2 - 4d\): \( \Large a + bi = \frac{\neg c + i \sqrt{4d - c^2}}{2} \) \( \Large a + bi = \neg \frac{c}{2} + \frac{\sqrt{4d - c^2}}{2} i \)
AccessDenied
  • AccessDenied
So, if we equate the like-parts here, we get: a = -c/2 b = sqrt(4d - c^2)/2 (The i's can divide off) From there, it takes some clever algebra work to get the two results you wanted to show. :)
anonymous
  • anonymous
okay that makes sense, but can you explain the "i", i dont understand why - 1 gets the imaginary part??

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

AccessDenied
  • AccessDenied
we factor out the -1 from under a square root, so the square root of the -1 = i \( \sqrt{c^2 - 4d} = \sqrt{(-1)(4d - c^2)} = \sqrt{-1}\sqrt{4d - c^2}\)
anonymous
  • anonymous
does "i" always equal -1 ?
AccessDenied
  • AccessDenied
\(i =\sqrt{-1}\), not just -1.
anonymous
  • anonymous
ohh i get it! thanks!
AccessDenied
  • AccessDenied
You're welcome! :) Were you able to figure out the rest?
anonymous
  • anonymous
im going to try it now
anonymous
  • anonymous
for quadratic formula, isnt its x= -b +/- square roots... why did you just write + ?
AccessDenied
  • AccessDenied
We're only dealing with one root when we use 'x = a + bi,' the positive square root here. The other root is 'x = a - bi', which is where the negative square root is used. Does that make sense?
anonymous
  • anonymous
yes!!
anonymous
  • anonymous
i got a^2 + b^2 = d, but i cant get 2a+c =0 2(-c/2) +\[\sqrt{4d-c ^{2}}\] =0 -c + d-c = 0?
AccessDenied
  • AccessDenied
hm... a = -c/2 Here we should have enough to get 2a + c = 0, we have all our variables in an equation! 2a = -c we can add c to both sides 2a + c = 0
anonymous
  • anonymous
yeaah! I didnt see that, I got it thanks so much!
AccessDenied
  • AccessDenied
You're welcome! :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.